Introduction to the Growers IPM Guide for Florida Tomato and Pepper Production - Norman C. Leppla (EDIS, 2008)
IPM-200, a 5-page illustrated fact sheet by N. C. Leppla, presents the IPM principles, past, present, and future of pest management in future, advantages of IPM, and project objectives. Includes references. Published by the UF Department of Entomology and Nematology, November 2007.